Nature conservation, protected areas and local communities : the Tsitsikamma National Park - Le Fleur, Yvette Adele (Rhodes University, Faculty of Humanities, Department of Anthropology)
Since the twentieth century, protected areas, usually in the form of nature reserves or national parks, have become increasingly more dominant as an international conservation strategy. An important factor in protected area management is the relationship between protected areas and its surrounding communities. Historically, the fortress conservation model based on the exclusion of human use and occupation prevailed in relation to protected areas. It is known that this approach brought with it many social and environmental injustices to local communities living in or adjacent to parks. However, a shift in conservation thinking occurred towards the end of the twentieth century, where it has increasingly been advocated for a more participatory approach in protected area management. South Africa has signed the international Convention on Biological Diversity that promotes a participatory approach to nature conservation, which is also reflected in the country's national laws and policies. In relation to the literature and the lens of political ecology, this thesis sets out to assess in what ways and to what extent the participatory approach has been embraced by South Africa's conservation authorities. As a case study, it looks at the Tsitsikamma National P ark ( incorporated into the larger Garden Route National Park). In order to get insight on h ow the participatory approach plays itself out at the T NP and what the nature of local communities' relationship with the park is, this study looks at the aspects of (1) local communities' socio-economic conditions, (2) their relationship with their natural environment, (3) their perception of nature conservation and (4) their perception of tourism. Then, taking all these aspects into account, (5) how local communities, in general, perceive their relationship with the p ark and its authorities. This study looked at the communities of Kurland, Nature's Valley, Covie and Storms River. It shows in concurrence with other studies, that despite progressive laws and policies that express the intention of the South African state and SANParks to embrace the participatory approach, its implementation o n t he g round is riddled with challenges.
Keywords: National parks and reserves -- South Africa -- Eastern Cape; Protected areas -- Management; Programme of Work on Protected Areas; Human ecology -- South Africa -- Tsitsikamma; Nature conservation -- Citizen participation